UJI KUALITAS YOGHURT SUSU SAPI DENGAN PENAMBAHAN MADU DAN Lactobacillus bulgaricus PADA KONSENTRASI YANG BERBEDA - Finarsih, Fita; Suparti, Suparti; Rahayu, Triastuti; Suryani, Titik (Tahta Media Group, 2025)
This study was motivated by the fact that cow’s milk is relatively affordable and widely consumed, yet it serves as an excellent growth medium for microorganisms, making it highly perishable. Therefore, processing and preservation through fermentation are necessary. One of the most popular fermented dairy products is yogurt, which is produced using lactic acid bacteria (LAB), particularly Lactobacillus bulgaricus, which plays an essential role in the fermentation process. Yogurt naturally has a sour taste; therefore, the addition of honey as a natural sweetener is needed to improve its acceptability. Honey contains approximately 41% fructose, 35% glucose, and 1.9% sucrose, which contribute to sweetness and may support fermentation activity. The objective of this study was to determine the effect of different concentrations of honey and Lactobacillus bulgaricus on the quality of cow’s milk yogurt. The research employed a Completely Randomized Design (CRD) with a two-factor factorial arrangement. The first factor was honey concentration (0%, 3%, and 5%), and the second factor was Lactobacillus bulgaricus concentration (0%, 3%, 5%, 7%, and 9%). The study also evaluated yogurt quality based on protein content, total acidity, and sensory attributes including color, aroma, taste, and overall acceptability through organoleptic testing. The results showed that both honey and Lactobacillus bulgaricus concentrations significantly affected yogurt quality. The lowest protein content was observed in treatment M1L1 (0% honey, 0% bacteria) at 2.94%, while the highest protein content was found in treatment M3L5 (5% honey, 9% bacteria) at 5.23%. Similarly, the lowest total acidity was recorded in M1L1 (0.61%), whereas the highest total acidity was obtained in M3L5 (1.65%). Yogurt treatments that were acceptable to panelists were those containing 5% honey combined with all bacterial concentrations (M3L1, M3L2, M3L3, M3L4, and M3L5).